Relationship quality and customer loyalty of Malaysian national carmakers - Saidin, Zainil Hanim; Saad, Rohaizah; Mohd Mokhtar, Sany Sanuri; Yusoff, Rushami Zien (2017)
Business organizations are losing customers and unable to attract new customers for various reasons.Studies have proven that the organizations with the unique competitive advantage are having benefit to retain the customer as well as attracting the new customer over the competitors. Relationship quality was identified as the intangible source of competitive advantage that ensures customer return for the long-term beneficial relationship.However, the difference in the context of study needs different measures of relationship quality to make up such quality that could bring different results to the level of customer loyalty.Therefore, the objective of this study is to investigate the influence of the relationship quality with industry-specific dimension on the level of customer loyalty in the context of Malaysian automotive industry. The systematic sampling using intercept survey design will be used.The sample of the study consists of the present individual customers of Malaysian national carmakers.